CFD simulation and measurement of the thermal behavior inside a room of the institutional library: a comparative study - Vázquez Silva, Efrén (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
This article presents the results of the comparison between the CFD simulation and temperature measurements, both in the time domain, at a certain point of interest within a specific closed space (cubicle) of the institutional library of the Salesian Polytechnic University (UPS), at its headquarters in the city of Cuenca, Republic of Ecuador. In this specific case, solar radiation is considered as the main heat transfer mechanism, which is why it was considered in the applied simulation method. An acceptable relative error was obtained between the simulated and measured temperature values. During the summer period, the thermal conditions inside the cubicle are not suitable for the comfort of the users. The study developed can constitute a basic tool for possible future research related to the implementation of climate conditioning for the cubicle, the library in general and any other site with similar constructive and operational characteristics.During the summer period, the thermal conditions inside the cubicle are not suitable for the comfort of the users. The study developed can constitute a basic tool for possible future research related to the implementation of climate conditioning for the cubicle, the library in general and any other site with similar constructive and operational characteristics.